SISTEM INFORMASI PENJUALAN PUPUK MENGGUNAKAN METODE APRIORI (STUDI KASUS PT PUPUK ISKANDAR MUDA) - Ahmad Ihsan; Rahmad Alfian Syahputra (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
Technological developments now provide many changes in every institution, from government to companies, all of which take advantage of technology that has brought great progress in various fields in every agency. Likewise with PT Pupuk Iskandar Muda. The purpose of the fertilizer sales application at PT Pupuk Iskandar Muda is so that workers can control the sales flow computerized and data is stored digitally so that it does not require a large storage space compared to being done manually. Of course, in designing and making this application, there are several steps that need to be done, namely by understanding the current system, formulating existing problems, then designing and making an information system that is able to solve ongoing problems.